Self-assembled Fe3O4 nanoparticle-doped TiO2 nanorod superparticles with highly enhanced lithium storage properties. Issue 3 (4th January 2018) - Xue, Bin; Li, Tongtao; Wang, Biwei; Ji, Li; Yang, Dong; Dong, Angang
Abstract : Self-assembled Fe3 O4 nanoparticle-doped TiO2 nanorod superparticles utilized as anode materials display highly enhanced performances for lithium-ion batteries. Abstract : Rational design of nanostructured anode materials is of importance for promoting the performance of lithium ion batteries (LIBs). Here the Fe3 O4 nanoparticles (NPs) were controllably inserted into the matrix of TiO2 nanorods (NRs) to obtain doped-superparticles (SPs) by a facile colloidal self-assembly route and subsequent calcination. To justify the effects of the doping, the lithium storage performances of the doped-SPs were evaluated as anode materials for LIBs. The results indicated that even a slight doping of Fe3 O4 NPs can effectively enhance the properties of the anode materials compared with raw TiO2 NR SPs. Additionally, the Fe3 O4 /(TiO2 )70 SPs showed an optimal performance in term of specific capacity, rate capacity, and cycling stability, whose reversible capacity maintained around 550 mA h g −1 at a current density of 1000 mA g −1 after 400 cycles. The highly enhanced lithium storage of the Fe3 O4 NP doped-TiO2 NR SPs can substantially be attributed to the synergism of the doped-superstructure, in which the individual merits of the Fe3 O4 NPs and TiO2 NRs are fully played out. This work not only demonstrates the significant effects of Fe3 O4 NP doping for TiO2 NR SP anode materials in LIBs, but also opens an avenue for the self-assembly synthesis of doped-SPs with extended applications.